Effects of interfacial reactions and electromigration on the Cu/electroless Ni-P/Sn-3.5Ag solder joint strength - Aditya Kumar (2008)
In this work, the effects of interfacial reactions and electromigration on the mechanical behavior of Cu/electroless Ni-P/Sn-3.5Ag solder joint were investigated. For a complete understanding, several process and material parameters, such as aging temperature, aging duration, Ni-P thickness, P concentration of Ni-P, and electric current density were varied systematically and their effect was studied on the solder joint strength.